Evaluation of the Implementation of Law No. 1 of 1970 on Occupational Safety: Challenges, Effectiveness, and Policy Recommendations - Ahmad, Iqbal Faza; Trisnantari, Sita Agung; Amrizal, Muhammad Dio Rhiza; Rozikin, Irkham Syahrul; Muhyiddin, Muhyiddin (Jurnal Ketenagakerjaan, 2024)
This policy analysis evaluates the implementation of Law No. 1 of 1970 on Occupational Safety in Indonesia, focusing on its effectiveness, challenges, and relevance in the Industry 4.0 era. With technological advancements and changing work conditions such as remote work and automation, the law is considered inadequate to address emerging risks. Using a qualitative approach, the analysis examines the legal framework, regulatory overlaps between the Ministry of Manpower and the Ministry of Health, and the effectiveness of field inspections. Findings reveal significant challenges in the law's implementation. Workplace safety inspections are suboptimal due to limited numbers and quality of inspectors and insufficient use of technology in monitoring. Several studies highlight how decentralized labor inspections at the provincial level lead to poor coordination and resource allocation. Additionally, penalties such as a maximum fine of IDR 100,000 fail to deter violators effectively. Recommendations include revising Law No. 1/1970 to address modern challenges, increasing the number and capacity of occupational safety inspectors, and adopting sensor-based real-time monitoring technologies. Stronger administrative sanctions, as seen in ISO 45001 standards, are necessary to enhance compliance. Training and awareness programs should also target SMEs with low compliance levels, ensuring improved workplace safety across industries.